Pengaruh Kompetensi dan Sarana Prasarana terhadap Motivasi Kerja serta Dampaknya pada Kinerja Guru di Sekolah Menengah Atas Negeri (SMAN) Kabupaten Muaro Jambi - Anisatuzzuhriah Anisatuzzuhriah; Osrita Hapsara; Ali Akbar; R. Adisetiawan (Universitas Batanghari Jambi, 2023)
The purpose of this research is to describe the competence, infrastructure, work motivation and efficiency of high school teachers in Muaro Jambi Regency. Then we analyze the effect of competence and tools on work motivation, analyze the effect of competence and tools on teacher performance, then analyze the effect of work motivation on teacher performance, then analyze the influence of competence and tools through the influence of work. teacher performance motivation. This research involved all 545 teachers at SMAN Muaro Jambi. A sample of 85 respondents based on the slovin formula with a confidence level of 1%. Data were analyzed using SPSS.22. The results showed that competence was in good condition, facilities and infrastructure were quite good, work motivation was high and teacher performance was also high, that competence and facilities together and partially had a positive and significant effect on work motivation, competence and facilities. Smultaneously and partially has a positive and significant effect on teacher effectiveness, and work motivation has a positive and significant effect on teacher effectiveness at SMAN Muaro Jambi Regency.